2016
DOI: 10.1155/2016/8469018
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration ofLactobacillus plantarum299v Reduces Cortisol Levels in Human Saliva during Examination Induced Stress: A Randomized, Double-Blind Controlled Trial

Abstract: Objective. To clarify the effect of Lactobacillus plantarum 299v on the salivary cortisol and salivary IgA levels in young adults under examination stress. Design. Forty-one students with an upcoming academic exam were included in a randomized double-blind, placebo-controlled study. The probiotic bacteria or the placebo product was administered in capsules once a day during 14 days. Saliva was collected and a perceived stress test was filled out at each sampling occasion. Saliva was collected for cortisol anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 29 publications
1
43
0
1
Order By: Relevance
“…Therefore, there is some indication that evening cortisol directly correlates with stress-associated disorders. Some studies have found an impact of probiotics on the cortisol response in stressed participants ( Chong et al, 2019 ), in particular in the response to exam stress ( Sawada et al, 2017 ; Kato-Kataoka et al, 2016 ; Andersson et al, 2016 ; Takada et al, 2016 ). Manipulation of the gut microbiota can therefore alter the neuroendocrine stress response through the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is some indication that evening cortisol directly correlates with stress-associated disorders. Some studies have found an impact of probiotics on the cortisol response in stressed participants ( Chong et al, 2019 ), in particular in the response to exam stress ( Sawada et al, 2017 ; Kato-Kataoka et al, 2016 ; Andersson et al, 2016 ; Takada et al, 2016 ). Manipulation of the gut microbiota can therefore alter the neuroendocrine stress response through the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of predominantly beneficial effects of probiotics in rodents are matched by some positive effects of different probiotic strains in humans. For instance, in a randomized, double-blind, placebo-controlled study, Lactobacillus plantarum 299v was administered to 41 students with an upcoming exam and associated with decreased corticosterone levels after 10 days [ 86 ]. Similarly, a probiotic formulation consisting of L. helveticus R0052 and B. longum R0175 (which had been effective in mice), decreased median urinary free cortisol levels and psychological distress, when given to 26 healthy volunteers for 30 days in a double-blind, controlled, randomized, parallel study [ 87 ].…”
Section: Pro- and Prebiotics As Mostly Beneficial Modulators Of The Nmentioning
confidence: 99%
“…Moreover, a connection has been established between the digestive tract and stress [291, 292]. Several studies that supplemented healthy young college students during exam preparation with probiotics ( L. plantarum 299v and L. casei Shirota) reported attenuation of cortisol compared to a control group [293295]. However, in an eight-week crossover design, 29 healthy male volunteers who supplemented with L. rhamnosus exhibited little difference in stress-related measures, HPA axis response, inflammation, or cognitive performance in comparison to placebo [296].…”
Section: Introductionmentioning
confidence: 99%